PENGARUH DAKWAH DIGITAL TIKTOK TERHADAP SIKAP BERIBADAH REMAJA MASJID DI DESA GAMBANGAN KEC. MAESAN KAB. BONDOWOSO - M.Hidayatullah; Sofyan Rofi; Hairul Huda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information technology has changed the pattern of delivering religious messages, one of which is through da'wah content on TikTok. This phenomenon requires adolescents to be able to filter and utilize digital da'wah content to improve the quality of worship attitudes in daily life. This study aims to determine the influence of TikTok digital da'wah on the worship attitude of mosque teenagers in Gambangan Village, Maesan District, Bondowoso Regency. The method used is quantitative with a sample of 50 respondents through a total sampling technique. Data collection was carried out using a closed-ended questionnaire on the scale of Likert which has been tested for validity and reliability. Data analysis includes instrument testing, classical assumption tests, as well as simple linear regression for hypothesis testing through the IBM SPSS Statistics 25 program. The results of the study showed that there was a positive and significant influence between TikTok digital da'wah on the worship attitude of mosque teenagers, as evidenced by a significance value of 0.000 (< 0.05). The value of the determination coefficient (R Square) of 0.365 indicates that TikTok's digital da'wah contributes 36.5% to the formation of adolescents' worship attitudes, while the remaining 63.5% is influenced by other factors outside the study. The regression equation obtained was Y = 23.392 + 0.465X, which showed that the improvement in the quality and intensity of digital da'wah content was followed by a consistent increase in adolescents' worship attitudes. The TikTok platform can be an effective da'wah medium if it is used optimally and responsibly in shaping the religious character of the younger generation.